Exploring the group holiday decision-making process with the support of technology. Issue 4 (July 2019) - Zhang, Lanyun; Sun, Xu; Wagner, Christian
Abstract: Numerous studies have examined the decision-making process and the associated information search behaviour of tourists. However, very few have focused on how tourists make plans for their trips when travelling in groups. This paper adds to the knowledge of the decision-making process of tourist groups with a specific focus on intra-group interaction and the support of technology. This research adopted a mixed-methods approach, combining two studies. Study 1 employed a focus group to gain an understanding of the decision-making process within a tourist group, while Study 2 employed a questionnaire survey to explore how the use of technology in such a process varies among different categories of groups. Study 1 proposed a model for a group holiday decision-making process with four components: information acquisition, intra-group information sharing, knowledge transfer, and decision making. It was adapted from the "Infogineering Model" and the encoding and decoding theory in communication studies. Study 2 identified new influential factors on the use of technology by tourist groups for decision making. Ultimately, this research produced a number of theoretical implications, as well as practical implications in terms of how practitioners can better support Chinese tourists, family travellers, and tourists with little prior travel experience, and how technology can facilitate group holiday decision making.